Effects of supplementing bile acids on the production performance, fatty acid and bile acid composition, and gut microbiota in transition dairy cows - Lei Li; Jiaxiao Li; Zhihui Liu; Zihan Jin; Mengyang Wang; Ying Wu; Zhihong Zhang; Xinfeng Hou; Junhu Yao; Jun Zhang (Journal of Animal Science and Biotechnology)
Abstract Background During the transition period, cows are prone to negative energy balance, which can lead to a decline in production performance and health in severe cases. In recent years, it has been discovered that bile acids (BAs) can act not only as fat emulsifiers but also as signaling molecules to regulate body metabolism. Although BAs have been used to some extent in monogastric and aquatic animals, their role in ruminants, particularly in transition cows, remains unclear. Therefore, this study aimed to determine the effects of BAs on the production performance, milk and plasma fatty acid and BA composition, and fecal microbiota in transition dairy cows. Results Forty-six healthy transition Holstein dairy cows with similar conditions were randomly divided into two groups and supplemented with 0 or 20 g/d of BAs from 21 d before the expected calving to 21 d after calving. The production performance was tracked until 60 d after calving. The results indicated that BA supplementation significantly improved postpartum milk fat content and yields as well as the yields of unsaturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids in milk. There was a significant increase in the concentration of triglyceride and the proportion of C ≤ 16 fatty acids in the plasma of cows supplemented with BAs, while the concentration of β-hydroxybutyrate and the proportion of C > 16 fatty acids in the plasma decreased significantly. BA supplementation significantly altered the composition of the fecal bacterial community and increased the relative abundance of bacteria beneficial for BA metabolism and transformation (Romboutsia, Clostridium sensu_stricto_6, and Clostridium sensu_stricto_1). Functional prediction analysis showed that the relative abundance of bile salt hydrolase, 7α-hydroxysteroid dehydrogenase, and BA inducible E as well as the pathways related to BA metabolism also significantly increased in cows supplemented BAs. In addition, BA supplementation significantly altered the composition of plasma and fecal BAs, particularly increasing circulating secondary BA concentration, which might induce the complete oxidation of fatty acids in the liver and further reduce the concentration of β-hydroxybutyrate. Conclusions These findings highlight the potential benefits of BA supplementation in improving milk yields and quality, as well as influencing metabolic pathways in transition dairy cows. Meanwhile, further studies are needed to elucidate the underlying mechanisms and explore the broader implications of these results by using more tissue samples.